0

I have an equation in the aligned environment to align the equal signs together. However, the last equation is too long, and I want to break it up. When I insert a linebreak, all the equations above the last one shift to the right. The code:

\begin{equation}
\begin{aligned}
\log\left(p\left(s|\alpha\right)\right) & = \sum\limits_{i=1}^O\left(\log\left(\frac{1}{\prod\limits_{k=1}^K\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)}\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(-\log\left(\prod\limits_{k=1}^K\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(\sum\limits_{k=1}^K\left(-\log\left(\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right)\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(\sum\limits_{k=1}^K\left(-\log\left(\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right)\right) + \log\left(\Gamma\left(\alpha_0\right)\right) -\log\left(\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right)
\end{aligned}
\end{equation}

What I want

\begin{equation}
\begin{aligned}
\log\left(p\left(s|\alpha\right)\right) & = \sum\limits_{i=1}^O\left(\log\left(\frac{1}{\prod\limits_{k=1}^K\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)}\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(-\log\left(\prod\limits_{k=1}^K\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(\sum\limits_{k=1}^K\left(-\log\left(\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right)\right) + \log\left(\frac{\Gamma\left(\alpha_0\right)}{\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)}\right) + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right) \\
&= \sum\limits_{i=1}^O\left(\sum\limits_{k=1}^K\left(-\log\left(\Gamma\left(\hat{\mathcal{S}}_k^i+1\right)\right)\right) + \log\left(\Gamma\left(\alpha_0\right)\right) -\log\left(\Gamma\left(\sum\limits_{k=1}^K\left(\hat{\mathcal{S}}_k^i+a_k\right)\right)\right) \\
\qquad\qquad + \log\left(\prod\limits_{k=1}^K \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma\left(\alpha_k\right)}\right)\right)
\end{aligned}
\end{equation}

I don't want to use &+ because then it gets aligned with the equal signs, and I want it indented a bit further.

2

&\qquad\qquad

But remember that a \left...\right cannot be broken, thus to have to rewrite the last to lines to say

  &=
    \sum\limits_{i=1}^O\Bigl(\sum\limits_{k=1}^K\left(-\log\left(\Gamma  \left(\hat{\mathcal{S}}_k^i+1\right)\right)\right)
      + \log\left(\Gamma\left(\alpha_0\right)\right)
      -\log\left(\Gamma\left(\sum\limits_{k=1}^K  \left(\hat{\mathcal{S}}_k^i+a_k\right)\right)\right)
      \\
      &\qquad\qquad + \log\left(\prod\limits_{k=1}^K
        \frac{\Gamma\left(\hat{\mathcal{S}}_k^i+\alpha_k\right)}{\Gamma   \left(\alpha_k\right)}\right)\Bigr)

With some more appropriate sizes.

Besides, are those massive ()'s really needed. To me they do not help much when ready the formula, instead they really annoy.


Addition, I would even go as far as (using mathtools) the code below. There is no need for all those autoscalling it ends up looking horrible. Also no need for those \limits.

\begin{equation}
  \begin{aligned}
    \MoveEqLeft
    \log\bigl(p(s|\alpha)\bigr) 
    \\
    & =
    \sum\limits_{i=1}^O\left(
      \log\Bigl(
        \frac{1}{\prod_{k=1}^K
          \Gamma(\hat{\mathcal{S}}_k^i+1)}
      \Bigr)
      +
      \log\Bigl(
        \frac{  
          \Gamma(\alpha_0)
        }{
          \Gamma\bigl(
          \sum_{k=1}^K(\hat{\mathcal{S}}_k^i+a_k)
          \bigr)
        }
      \Bigr)
      + \log\Bigl(
        \prod_{k=1}^K
        \frac{
          \Gamma(\hat{\mathcal{S}}_k^i+\alpha_k)
        }{
          \Gamma(\alpha_k)
        }
      \Bigr)
    \right)
    \\
    &=
    \sum\limits_{i=1}^O
    \left(
      -\log\Bigl(
        \prod_{k=1}^K
        \Gamma(\hat{\mathcal{S}}_k^i+1)
      \Bigr)
      +
      \log\Bigl(
        \frac{
          \Gamma(\alpha_0)
        }{
          \Gamma\bigl(
            \sum_{k=1}^K
            (\hat{\mathcal{S}}_k^i+a_k)
          \bigr)
        }
      \Bigr)
      + \log\Bigl(
        \prod_{k=1}^K
        \frac{
          \Gamma(\hat{\mathcal{S}}_k^i+\alpha_k)
        }{
          \Gamma(\alpha_k)
        }
      \Bigr)
    \right)
    \\
    &=
    \sum_{i=1}^O
    \left(
      \sum_{k=1}^K
      \Bigl(
        -\log
        \bigl(\Gamma(\hat{\mathcal{S}}_k^i+1) \bigr)
      \Bigr)
      +
      \log\Bigl(
        \frac{
          \Gamma(\alpha_0)
        }{
          \Gamma\bigl(
          \sum_{k=1}^K
            (\hat{\mathcal{S}}_k^i+a_k)
            \bigr)
          }
        \Bigr)
      + \log\Bigl(
        \prod_{k=1}^K
        \frac{
          \Gamma(\hat{\mathcal{S}}_k^i+\alpha_k)
        }{
          \Gamma(\alpha_k)
        }
      \Bigr)
    \right)
    \\
    &=
    \sum_{i=1}^O\Biggl(
    \sum_{k=1}^K
    \Bigl(
      -\log\bigl(
      \Gamma(\hat{\mathcal{S}}_k^i+1)
      \bigr)
    \Bigr)
    + \log\left(
      \Gamma(\alpha_0 )
    \right)
    -\log\biggl(
      \Gamma\Bigl(
      \sum_{k=1}^K
      (\hat{\mathcal{S}}_k^i+a_k)
      \Bigr
      )
    \biggr)
    \\
    &\qquad\qquad + \log\Bigl(
    \prod_{k=1}^K
    \frac{
      \Gamma(\hat{\mathcal{S}}_k^i+\alpha_k)
    }{
      \Gamma(\alpha_k)
    }
    \Bigr)
    \Biggr)
  \end{aligned}
\end{equation}

Or even better, don't write it all out. It does not help the reader. Define helpers:

So ease notation, we define:
\begin{align*}
  A &= \prod_{k=1}^K  \Gamma(\hat{\mathcal{S}}_k^i+1) \\
  B &= \sum_{k=1}^K(\hat{\mathcal{S}}_k^i+a_k)\\
  C &= \prod_{k=1}^K  \frac{ \Gamma(\hat{\mathcal{S}}_k^i+\alpha_k)}{ \Gamma(\alpha_k) }
\end{align*}



\begin{equation}
  \begin{aligned}
    \MoveEqLeft
    \log\bigl(p(s|\alpha)\bigr) 
    \\
    & =
    \sum\limits_{i=1}^O\left(
      \log\Bigl( \frac{1}{A}  \Bigr)
      +
      \log\Bigl(
        \frac{  
          \Gamma(\alpha_0)
        }{
          \Gamma\bigl(
          B
          \bigr)
        }
      \Bigr)
      + \log(C)
    \right)
    \\
    &=
    \sum\limits_{i=1}^O
    \left(
      -\log( A )
      +
      \log\Bigl(
        \frac{ \Gamma(\alpha_0) }{ \Gamma( B ) }
      \Bigr)
      + \log( C )
    \right)
    \\
    &=
    \sum_{i=1}^O
    \left(
      \sum_{k=1}^K
      \Bigl(
        -\log
        \bigl(\Gamma(\hat{\mathcal{S}}_k^i+1) \bigr)
      \Bigr)
      +
      \log\Bigl(
        \frac{ \Gamma(\alpha_0) }{ \Gamma( B ) }
        \Bigr)
      + \log( C  )
    \right)
    \\
    &=
    \sum_{i=1}^O\biggl(
    \sum_{k=1}^K
    \Bigl(
      -\log\bigl(
      \Gamma(\hat{\mathcal{S}}_k^i+1)
      \bigr)
    \Bigr)
    + \log\left(
      \Gamma(\alpha_0 )
    \right)
    -\log\bigl(
      \Gamma( B )
    \bigr)
    + \log( C )
    \biggr)
  \end{aligned}
\end{equation}

enter image description here

  • 1
    Thanks a lot for the extra edit, that does look much better. – Niek Oct 8 '13 at 10:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.